2012
DOI: 10.5812/numonthly.4225
|View full text |Cite
|
Sign up to set email alerts
|

Mineral and Bone Disease in Black African Hemodialysis Patients: A Report From Senegal

Abstract: BackgroundChronic kidney disease related mineral and bone disease (CKD-MBD) is a worldwide challenge in hemodialysis patients. In Senegal, number of dialysis patients is growing but few data are available about their bone disorders.ObjectivesTo describe patterns of CKD-MBD in Senegalese dialysis patients.Patients and MethodsWe performed a cross-sectional study including patients from three dialysis centres in Senegal. Diagnosis of different types of CKD-MBD relied on clinical, biological and radiological data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 19 publications
4
22
0
Order By: Relevance
“…In agreement with previous studies from Africa and developed countries [7][8][9] , this study has revealed a high prevalence of derangements of biochemical markers of mineral bone disorder. Based on the cut-off values utilized by this study, hyperparathyroidism (PTH>150) was present in 73.4% of the patients and 37% with a stricter cut-off value of 585 ng/ml(9 times the upper normal of our laboratory assay ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In agreement with previous studies from Africa and developed countries [7][8][9] , this study has revealed a high prevalence of derangements of biochemical markers of mineral bone disorder. Based on the cut-off values utilized by this study, hyperparathyroidism (PTH>150) was present in 73.4% of the patients and 37% with a stricter cut-off value of 585 ng/ml(9 times the upper normal of our laboratory assay ).…”
Section: Discussionsupporting
confidence: 80%
“…In addition, we found phosphataemia to have remained closely related to log-transformed PTH in multivariate linear regression. The strength of our study is the larger sample size compared to other previous studies from Africa 7,9,25 .…”
Section: Discussionmentioning
confidence: 80%
“…The first group low-turnover renal osteopathy (adynamic bone disease), the second was the optimal group, target of the NKF-KDOQI and the third high turnover bone disease (2 nd hyperparathyroidism), the three groups represented by 27%, 23% and 50% respectively. Comparable results obtained by other studies, 30%, 25%, 45%, respectively (34), 13%, 22%, 55%, respectively (35), likewise 18%, 33% and 49% respectively (36). However, these results expressed need for more expensive medication to control secondary hyperparathyroidism to achieve the target of the NKF -KDOQI.…”
Section: Summary Of Qol Responses In In Different Study Groupssupporting
confidence: 62%
“…Only associations toward worsened QOL variables were found with increasing HD duration and iPTH level respectively; functional status (r=0.37; P=0.05) (r=0. 36 …”
Section: Correlation Between Qol and Study Parametersmentioning
confidence: 99%
“…CKD-related MBD (CKD-MBD) is a worldwide challenge in hemodialysis patients [9]. CKD is characterized by the decline of kidney function within long period [10].…”
Section: Resultsmentioning
confidence: 99%